Bending behavior and its effect on switching performance of an all-optical switch. (1st February 2021) - Wang, K F; Wang, B L; Zheng, L; Zhang, Y; Zhang, C W
Abstract: The all-optical switch is one of the key elements of all-optical high speed information networks and computing systems. Their bending behavior, actuated by optical gradient forces, dramatically influences their switching performance and is therefore the research topic of this paper. The coupled behavior between optical gradient forces and the bending deflection is taken into account in the present model. The effects of the effective refractive index and the stretching induced by bending are included and their influences on the resonance wavelength shift of the signal light are discussed. Results show that the resonance wavelength shift increases almost linearly at first, and then increases suddenly as the circulating power increases. The resonance wavelength shift increases as the central angle of the suspended part increases, while it decreases with the initial gap. The present theoretical model may be helpful when designing all-optical switches.